(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The main idea of the article is devoted to the comparison and analysis of the experience of Uzbekistan and abroad in the formation of pedagogical responsibility among future defectologists. Important ways of developing the pedagogical responsibility of Future defectologists are discussed, including practical training, independent study and Research activities.